The progressive and rational occupation of the urban system boundary: entropies in La Azucena, Mexico - González Pérez, Mario Guadalupe; Serafin González, Sylvia Lorena; de Haro de León, Liliana; Flores, Susana Marceleño; Lizcano Caro, José Andelfo (Acta Universitaria, 2019)
This is a study about the experience of dwelling in the boundary of the metropolitan area in Guadalajara, Mexico, a place in which there have been various housing scenarios considered as progressive and rational with isomorphic traits, as it is the case of La Azucena. The aim of the article is to identify the hostile forces that peri-urban residents face and the impact that these anthropic forces may produce in the process of inhabiting those periurban areas. In this context, it was necessary to build an index of occupancy using the statistics application SPSS for obtaining a later georeference using the program ArcMap. Thus, it was obtained the Index of Kaiser-Mayer-Olkin and the sphericity test given by Barlett for these three established measurements: health, education and occupancy. In the conceptual precepts of the systems, there are some complex interactions based on the processes of peri-urban planning.